Brazilian federal institutes – potentials and challenges for public VET’s reputation - Annen, Silvia [Verfasser]; Sabrina Sailer-Frank [Verfasser]; Schiedeck, Claudia [Verfasser] (My University, 2024)
“Vocational Education and Training (VET) faces significant global challenges, particularly due to its varying reputation and the preference for academic professions, which are associated with higher social status and salaries. This issue is especially pronounced in Brazil, where VET participation is low and dropout rates are high. The division between public and private VET institutions has resulted in a mixed reputation nationwide. Federal Institutes (FIs), which offer public and tuition-free education, face challenges in terms of acceptance and reputation, while private, fee-based VET institutions enjoy high enrollment rates. This research aims to identify not only the challenges faced by the FIs but also the opportunities they have as unique stakeholders in Brazil’s educational landscape. The focus of the study is on the role FIs can play in enhancing the reputation of public VET, with an analysis of educational governance, institutional frameworks, and their relevance to the skills ecosystem approach.” (authors’ abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.3.3 Lateinamerika; 370; Berufsbildung; Berufsbildungssystem; Berufsbildungspolitik; Institution; Bildungseinrichtung; Brasilien